Multi-scale characterization and biological evaluation of composite surface layers produced under glow discharge conditions on NiTi shape memory alloy for potential cardiological application. (November 2018) - Chlanda, Adrian; Witkowska, Justyna; Morgiel, Jerzy; Nowińska, Katarzyna; Choińska, Emilia; Swieszkowski, Wojciech; Wierzchoń, Tadeusz
Highlights: Oxidation in low-temperature plasma created nanocrystalline TiO2 -titanium oxide (rutile) surface layers on NiTi alloy. The surface layers were characterized by varying surface topography, wettability, and surface free energy. Combining a TiO2 layer and a carbon layer may increase NiTi alloy biocompatibility for cardiological applications. Abstract: NiTi shape memory alloys are characterized by relatively good biocompatibility primarily thanks to their ability to self-passivate. However, before they can be used as medical implants for long term use, they need to undergo treatment aimed at producing layers on their surface that are superior to spontaneously formed oxide layers and that would increase their resistance to corrosion, limit nickel ion release from the surface (metallosis) and have the capability to shape their biological properties depending on the application. Furthermore, cardiac implants require addressing the issue of blood clotting on the surface. Treatment in glow-discharge low temperature plasma makes it possible to produce titanium layers with a structure and properties that are controlled via process parameters. In addition, antithrombogenic properties can be improved by depositing a carbon coating via the RFCVD process. The aim of the study was to investigate the structure, surface topography, adhesive properties, wettability, surface free energy and evaluate metallosis after producing TiO2 and a-C:N:H + TiO2 composite layers on NiTi alloy. The capabilities of AFM microscopes in studying the adhesive properties of a surface were also highlighted in the study. The study shows that the produced surface layers are capable of significantly reducing metallosis. Furthermore, in contrast to NiTi in its initial state, layers of nanocrystalline TiO2 titanium oxide (rutile) with a homogeneous structure demonstrate greater adhesion strength and more developed surface in the microscale, which facilitates the formation of an a-C:N:H coating. Therefore the formation of a coating of a-C:N:H amorphous carbon on NiTi alloy that has previously been oxidised in low-temperature plasma may prove to be a favourable solution in terms of using NiTi alloy to produce cardiac implants.